The Philippines in the emerging world environment : globalization at a glance - Paderanga, Cayetano W. (Quezon City : U.P., Center for Integrative & Development Studies and the U.P. Press, 1996)
Includes bibliographical references and index.
Keywords: Philippines -- Economic conditions -- 1986-.; Philippines -- Economic policy; Philippines -- Foreign economic relations